Benefits and Harms of Hypertension and High-Normal Labels: A Randomized Experiment. Issue 4 (5th April 2021) - Muscat, Danielle Marie; Morris, Georgina May; Bell, Katy; Cvejic, Erin; Smith, Jenna; Jansen, Jesse; Thomas, Rae; Bonner, Carissa; Doust, Jenny; McCaffery, Kirsten
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Recent US guidelines lowered the threshold for diagnosing hypertension while other international guidelines use alternative/no labels for the same group (blood pressure [BP], <140/90 mm Hg). We investigated potential benefits and harms of hypertension and high-normal BP labels, compared with control, among people at lower risk of cardiovascular disease. Methods: We conducted a randomized experiment using a national sample of Australians (n=1318) 40 to 50 years of age recruited from an online panel. Participants were randomized to 1 of 3 hypothetical scenarios where a general practitioner told them they had a BP reading of 135/85 mm Hg, using either hypertension/high-normal BP/control (general BP description) labels. Participants were then randomized to receive an additional absolute risk description or nothing. Primary outcomes were willingness to change diet and worry. Secondary outcomes included exercise/medication intentions, risk perceptions, and other psychosocial outcomes. Results: There was no difference in willingness to change diet across label groups ( P =0.22). The hypertension label (mean difference [MD], 0.74 [95% CI, 0.41–1.06]; P <0.001) and high-normal BP label (MD, 0.45 [95% CI, 0.12–0.78]; P =0.008) had increased worry about cardiovascular disease risk compared with control. There was no evidence that either label increased willingness to exercise ( P =0.80). However, the hypertension (MD, 0.20 [95% CI, 0.04–0.36]; P =0.014), but not high-normal label (MD, 0.06 [95% CI, −0.10 to 0.21]; P =0.49), increased willingness to accept BP-lowering medication compared with control. Psychosocial differences including lower control, higher risk perceptions, and more negative affect were found for the hypertension and high-normal labels compared with control. Providing absolute risk information decreased willingness to change diet (MD, 0.25 [95% CI, 0.10–0.41]; P =0.001) and increase exercise (MD, 0.28 [95% CI, 0.11–0.45]; P =0.001) in the hypertension group. Conclusions: Neither hypertension nor high-normal labels motivated participants to change their diet or exercise more than control, but both labels had adverse psychosocial outcomes. Labeling people with systolic BP of 130 to 140 mm Hg, who are otherwise at low risk of cardiovascular disease, may cause harms that outweigh benefit. Registration: URL: http://www.anzctr.org.au/ ; Unique identifier: ACTRN12618001700224.